Effectiveness of obstetric point-of-care ultrasound (POCUS) training: a systematic review and meta-analysis based on the ADDIE training model - Li, Yuxuan; Wang, Hao; Yuan, Kang; Zhou, Xiaoding; Wang, Mengting; Huang, Yiyang; Yu, Xinyi; Tang, Kun (The Ultrasound Journal, 2025)
Aim: To identify the core components of obstetric point-of-care ultrasound (POCUS) training programs while simultaneously evaluating the effectiveness of these programs using the Analyze, Design, Develop, Implement, and Evaluate (ADDIE) model.Methods: This systematic review and meta-analysis followed a PROSPERO-registered protocol (CRD42024566260) and adhered to PRISMA2020, Cochrane Handbook, and JBI Manual guidelines. Comprehensive searches from database inception to September 22, 2024, covered international and Chinese databases to identify studies evaluating obstetric POCUS training. Two independent reviewers screened studies, assessed methodological quality with JBI tools, and extracted data on study, participant, intervention, and outcome characteristics. Training content was mapped to the ADDIE instructional design model via thematic and framework analyses. Meta-analyses of comparable quantitative outcomes used random-effects models. Integrating quantitative and qualitative findings, this review systematically evaluated the effectiveness and implementation of obstetric POCUS training programs.Results: Systematic synthesis showed that obstetric POCUS training significantly improved healthcare providers’ competencies, including knowledge, skills, sustained use, and clinical decision-making. Training also increased antenatal care attendance and identification of high-risk pregnancies, while reducing referrals and optimizing resource use. However, limitations were noted in needs assessment, implementation flexibility, and outcome evaluation. Using thematic and framework analyses combined with the ADDIE model, we systematically organized training phases and key components to provide a scientific basis for program improvement and optimization.Conclusions: Obstetric POCUS training effectively enhances clinical competencies and improves maternal and neonatal health outcomes. Applying the ADDIE model offers a replicable, practical, and sustainable approach for developing standardized training programs. Future obstetric POCUS training should leverage the ADDIE model and adapt to local contexts to improve maternal and neonatal health globally.